2018
DOI: 10.18174/450223
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable cocoa in Côte d'Ivoire : The impacts and contribution of UTZ certification combined with services provided by companies

Abstract: The impacts and contribution of UTZ certification combined with services provided by companies 2 | Wageningen Economic Research Report Ingram, V., van Rijn, F., Waarts, Y., Dekkers, M., de Vos, B., Koster, T., Tanoh R., Galo A. 2017 The user may reproduce, distribute and share this work and make derivative works from it. Material by third parties which is used in the work and which are subject to intellectual property rights may not be used without prior permission from the relevant third party. The user must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…As for CFI, it stands for a joint public-private partnership between the cocoa industry and the government of Côte d'Ivoire and Ghana to establish zero-deforestation by promoting cocoa agroforestry among other sustainable initiatives. The fact that trends emerged from this six-year-old study about potential obstacles-farmer age and gender, technical knowledge and skill, land tenure and ownership, availability of financial resources and seedlings of companion treeslikely to impede the adoption of agroforestry by cocoa farmers meet the conclusions of several studies recently rolled out in the same region for a sustainable cocoa sector [20,79], confirmed not only the relevance of this work, but also its contribution to promoting agroecological transition in cocoa farming.…”
Section: Discussionmentioning
confidence: 53%
“…As for CFI, it stands for a joint public-private partnership between the cocoa industry and the government of Côte d'Ivoire and Ghana to establish zero-deforestation by promoting cocoa agroforestry among other sustainable initiatives. The fact that trends emerged from this six-year-old study about potential obstacles-farmer age and gender, technical knowledge and skill, land tenure and ownership, availability of financial resources and seedlings of companion treeslikely to impede the adoption of agroforestry by cocoa farmers meet the conclusions of several studies recently rolled out in the same region for a sustainable cocoa sector [20,79], confirmed not only the relevance of this work, but also its contribution to promoting agroecological transition in cocoa farming.…”
Section: Discussionmentioning
confidence: 53%
“…Calkins and Ngo [99] observe that these effects may spread to surrounding areas, thus strengthening communities by becoming local service providers where the public sector may be lacking. In Côte d'Ivoire, many companies target these farmers with affiliations to a cooperative or establish new links, excluding a large number of farmers from access to finance and other support, such as training and inputs [100]. However, the alignment of cooperatives' activities with the expectation of external actors, such as multinational corporations or certification organizations, comes with the risk of creating strong dependencies of cooperatives on external resources and the audit of requirements.…”
Section: Côte D'ivoirementioning
confidence: 99%
“…The industry’s pledge to reduce child labour in Ghana and Côte d’Ivoire by 70% had not been met as of late 2015, and the deadline was extended to 2020. Harkin–Engel stimulated a variety of new initiatives and programmes by governments, international agencies (Khan and Murray, 2007), firms (Nestle Cocoa Plan and ICI, 2017), certification bodies (Ingram et al, 2017) and NGOs.…”
Section: What Goes Around Comes Aroundmentioning
confidence: 99%